(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Integrated education aimed at the formation of creative activity requires the goal, task, content, form, methods and tools, as well as the result, to be integrated in the implementation of this process, and the creation of interrelationship and dependence between all structural bases of the creative process.